2021
DOI: 10.3389/fpsyg.2021.703598
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Emerging Number Knowledge in Toddlers

Abstract: Recent evidence suggests that infants and toddlers may recognize counting as numerically relevant long before they are able to count or understand the cardinal meaning of number words. The Give-N task, which asks children to produce sets of objects in different quantities, is commonly used to test children’s cardinal number knowledge and understanding of exact number words but does not capture children’s preliminary understanding of number words and is difficult to administer remotely. Here, we asked whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…If this difference is not caused by random noise and if the hypothesis test missed the difference only due to the lack of power, then this difference should be interpreted. One possible explanation builds on the findings that children have partial knowledge of the numbers immediately beyond their known number range (Barner & Bachrach, 2010; Gunderson et al., 2015; Krajcsi & Fintor, 2023; O'Rear et al., 2020; Silver et al., 2021; K. Wagner et al., 2019). For example, a four‐knower may have some partial knowledge of the number 5.…”
Section: Resultsmentioning
confidence: 99%
“…If this difference is not caused by random noise and if the hypothesis test missed the difference only due to the lack of power, then this difference should be interpreted. One possible explanation builds on the findings that children have partial knowledge of the numbers immediately beyond their known number range (Barner & Bachrach, 2010; Gunderson et al., 2015; Krajcsi & Fintor, 2023; O'Rear et al., 2020; Silver et al., 2021; K. Wagner et al., 2019). For example, a four‐knower may have some partial knowledge of the number 5.…”
Section: Resultsmentioning
confidence: 99%
“…Children viewed a series of paired images on the computer screen and for each, were asked to point to the one (left or right side) that showed the number of objects queried (Silver et al, 2021; Appendix A). To familiarize children with the task, children were given two practice trials with two different common objects and prompted to point to one image (e.g., ‘Which has a ball?’).…”
Section: Methodsmentioning
confidence: 99%
“…Whereas web-based data collection in adults is extensively and successfully used and several well-established RT effects have been replicated in web-based research ( Crump et al, 2013 ; Simcox and Fiez, 2014 ), there are only a few recent web-based studies with children and infants ( Scott et al, 2017 ; Nussenbaum et al, 2020 ; Rhodes et al, 2020 ; Bambha and Casasola, 2021 ; Vales et al, 2021 ). Recent studies collecting RTs with adults and children have shown little to no difference between laboratory-based and web-based samples ( de Leeuw and Motz, 2016 ; Hilbig, 2016 ; Bridges et al, 2020 ; Nussenbaum et al, 2020 ; Morini and Blair, 2021 ; Silver et al, 2021 ; Vales et al, 2021 ) as well as no big differences between browsers (e.g., Chrome and Internet Explorer) or experiment builders (e.g., Pavlovia and Gorilla) ( Kochari, 2019 ; Anwyl-Irvine et al, 2020 ; Sauter et al, 2020 ). In addition, it is difficult to clearly state whether potential differences may be any greater than the difference between two laboratory-based collected samples ( Nussenbaum et al, 2020 ).…”
Section: Natural Stimulimentioning
confidence: 99%